Risk of developing depression from endocrine treatment: A nationwide cohort study of women administered treatment for breast cancer in South Korea - Oh, Jooyoung; Lee, Hye Sun; Jeon, Soyoung; Kim, Dooreh; Seok, Jeong-Ho; Park, Woo-Chan; Kim, Jae-Jin; Yoon, Chang Ik (Frontiers in Oncology, 2022)
Background Although previous studies demonstrated no association between depression and tamoxifen in patients with breast cancer, there is still a limited amount of long-term follow-up data. This study aimed to evaluate the relationship between endocrine treatment and the risk of depression. Methods This nationwide population-based cohort study used data obtained over a 14-year period (January 2007 to December 2021) from the Korean National Health Insurance claims database. All female patients with breast cancer were included. We examined the incidence of depression in patients who underwent endocrine treatment, and those who did not undergo endocrine treatment constituted the control group. Results The data from 11,109 patients who underwent endocrine treatment and 6,615 control patients between 2009 and 2010 were analyzed. After performing matching for comorbidities and age, both groups comprised 6,532 patients. The median follow-up were 119.71 months. Before and after matching was performed, the endocrine treatment was not a significant risk factor for developing depression (p=0.7295 and p=0.2668, respectively), nor was it a significant factor for an increased risk for suicide attempt (p=0.6381 and p=0.8366, respectively). Conclusions Using a real-world population-based cohort, this study demonstrated that there is no evidence that the endocrine treatment increases the risk of depression.